2014
DOI: 10.2308/bria-50707
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Principles-Based versus Rules-Based Accounting Standards on Auditors' Motivations and Evidence Demands

Abstract: Auditing research has investigated the effects of different accounting standards on auditors' decisions to constrain aggressive reporting by clients. Missing from this literature is evidence on how the type of accounting standard influences auditors' cognitive motivations and demand for audit evidence. This study addresses this gap in the literature, which is important since the financial statements are the joint product of management's and the auditor's actions. An experiment was conducted with U.S. and Dutch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
59
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(65 citation statements)
references
References 48 publications
3
59
1
2
Order By: Relevance
“…Taken together, our research provides a contribution to the related work in this area by Cohen et al (2013) and Peytcheva et al (2014) in several important areas. First, our research scope is different and very appropriate to look at the effect of IFRS.…”
Section: Introductionmentioning
confidence: 52%
See 4 more Smart Citations
“…Taken together, our research provides a contribution to the related work in this area by Cohen et al (2013) and Peytcheva et al (2014) in several important areas. First, our research scope is different and very appropriate to look at the effect of IFRS.…”
Section: Introductionmentioning
confidence: 52%
“…Recent studies on this topic have found that under principlesbased accounting standards, auditors are more likely to constrain aggressive reporting (Cohen, Krishnamoorthy, Peytcheva, & Wright, 2013) and increase process accountability, epistemic motivation, and demand for evidence (Peytcheva, Wright, & Majoor, 2014). Our study adds to prior research by investigating how auditors play their role in the implementation of principles-based versus rules-based accounting standards in China, which is an environment where auditors have experienced recent changes to accounting standards.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations